Independence of the blood pressure lowering effect and efficacy of the angiotensin receptor neprilysin inhibitor, LCZ696, in patients with heart failure with preserved ejection fraction: an analysis of the PARAMOUNT trial. (1st April 2014) - Jhund, Pardeep S.; Claggett, Brian; Packer, Milton; Zile, Michael R; Voors, Adriaan A.; Pieske, Burkert; Lefkowitz, Martin; Shi, Victor; Bransford, Toni; McMurray, John J. V.; Solomon, Scott D
<x xml:space="preserve">Abstract</x> Aims The first in class angiotensin receptor neprilysin inhibitor, LCZ696 has been shown to reduce levels of N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), reduce left atrial size and improve New York Heart Association (NYHA) class in patients with heart failure with preserved ejection fraction (HFpEF). We examined whether the effects of LCZ696 were independent of systolic blood pressure (SBP) lowering. Methods and results In the Prospective comparison of ARNi (angiotensin receptor neprilysin inhibitor) with ARB (angiotensin receptor blocker) on Management Of heart failUre with preserved ejectioN fracTion (PARAMOUNT) trial 301 patients were randomly assigned to LCZ696 or valsartan. We examined the relationship between SBP lowering and LCZ696 on NT‐proBNP level, left atrial size, NYHA class and estimated glomerular filtration rate (eGFR). By 12 weeks blood pressure was reduced by 9 mmHg (SD 15)/5 mmHg (SD 11) in patients receiving LCZ696 in comparison with 3 mmHg (SD 17)/2 mmHg (SD 12) in those receiving valsartan. The change in NT‐proBNP was poorly correlated with change in SBP (LCZ696, r = 0.17, P = 0.06; valsartan, r = 0.05, P = 0.58) After adjustment for change in SBP, the ratio of change in NT‐proBNP at 12 weeks for LCZ696 vs. valsartan was 0.76 (95% CI 0.63–0.93, P = 0.008), and similar to the ratio not adjusting for SBP (0.76, 95% CI 0.63–0.92, P = 0.006); P for interaction was 0.38). Similarly, reduction in left atrial volume index at 36 weeks, improvement in NYHA class and eGFR were all independent of the change in SBP. Conclusion In patients with HFpEF, the effect of the angiotensin receptor neprilysin inhibitor LCZ696 on NT‐proBNP, left atrial volume, functional class, and eGFR was independent of reduction in SBP.